Template‐based and free modeling of I‐TASSER and QUARK pipelines using predicted contact maps in CASP12. (14th November 2017) - Zhang, Chengxin; Mortuza, S. M.; He, Baoji; Wang, Yanting; Zhang, Yang
Abstract: We develop two complementary pipelines, "Zhang‐Server" and "QUARK", based on I‐TASSER and QUARK pipelines for template‐based modeling (TBM) and free modeling (FM), and test them in the CASP12 experiment. The combination of I‐TASSER and QUARK successfully folds three medium‐size FM targets that have more than 150 residues, even though the interplay between the two pipelines still awaits further optimization. Newly developed sequence‐based contact prediction by NeBcon plays a critical role to enhance the quality of models, particularly for FM targets, by the new pipelines. The inclusion of NeBcon predicted contacts as restraints in the QUARK simulations results in an average TM‐score of 0.41 for the best in top five predicted models, which is 37% higher than that by the QUARK simulations without contacts. In particular, there are seven targets that are converted from non‐foldable to foldable (TM‐score >0.5) due to the use of contact restraints in the simulations. Another additional feature in the current pipelines is the local structure quality prediction by ResQ, which provides a robust residue‐level modeling error estimation. Despite the success, significant challenges still remain in ab initio modeling of multi‐domain proteins and folding of β‐proteins with complicated topologies bound by long‐range strand‐strand interactions. Improvements on domain boundary and long‐range contact prediction, as well as optimal use of the predicted contacts and multiple threading alignments, are critical to address these issues seen in the CASP12 experiment.